Ambipolar Graphene–Quantum Dot Phototransistors with CMOS Compatibility. Issue 23 (4th October 2018) - Zheng, Li; Zhou, Wenjia; Ning, Zhijun; Wang, Gang; Cheng, Xinhong; Hu, Weida; Zhou, Wen; Liu, Zhiduo; Yang, Siwei; Xu, Kaimin; Luo, Man; Yu, Yuehui
Abstract: The hybridization of 2D materials and colloidal quantum dots (CQDs) has been demonstrated to be an ideal platform for infrared photodetectors due to the high mobility of 2D materials and the excellent light harvesting capability of CQDs. However, the realization of ambipolar, broadband, and room‐temperature graphene–quantum dot phototransistors with complementary metal–oxide–semiconductor (CMOS) compatibility remains challenging. Here N, S codecorated graphene is deposited with PbS CQDs to fabricate a hybrid phototransistor on a silicon dioxide/silicon gate. The resulting device demonstrates a gate‐tuneable ambipolar feature with a low gate bias of less than 3.3 V at room temperature in ambient. Broadband spectra from visible to near‐infrared and to short wave infrared (SWIR) light can be detected with gain value of up to 10 5 and a fast response of 3 ms. Upon illumination by SWIR light at 1550 nm, the phototransistor exhibits an ultrahigh responsivity that is on the order of 10 4 AW −1 and a specific detectivity that is on the order of 10 12 Jones with a low driving voltage of 1 V. This decorated hybrid architecture illustrates the potential of graphene and CQDs to be integrated with silicon integrated circuits and opens a new path toward ambipolar photodetector fabrication. Abstract : N, S codecorated graphene deposited with PbS colloidal quantum dots (CQDs) is adopted to fabricate a phototransistor. It demonstrates a gate‐tunable ambipolar feature with a low gate bias of less than 3.3 V. Broadband spectra from visible to short wave infrared (SWIR) can be detected with an ultrahigh gain of 10 5, a fast response of 3 ms, and a sensitive responsivity of 10 4 AW −1 .